2007
DOI: 10.1093/nar/gkm1052
|View full text |Cite
|
Sign up to set email alerts
|

ATR-dependent pathways control hEXO1 stability in response to stalled forks

Abstract: Nucleases play important roles in DNA synthesis, recombination and repair. We have previously shown that human exonuclease 1 (hEXO1) is phosphorylated in response to agents stalling DNA replication and that hEXO1 consequently undergoes ubiquitination and degradation in a proteasome-dependent manner. In the present study, we have addressed the identity of the pathway transducing stalled-replication signals to hEXO1. Using chemical inhibitors, RNA interference, ATM- and ATR-deficient cell lines we have concluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 40 publications
(50 reference statements)
6
74
0
Order By: Relevance
“…DDK is therefore required for the initiation of replicationcheckpoint activation, and we also show for the recovery of stalled forks. An active replicationcheckpoint would then attenuate nucleolytic activity at stalled forks to prevent excessive degradation of DNA by described mechanisms [41,[47][48][49]. Budding yeast cells lacking the checkpoint kinase Rad53, which inhibits DDK, exhibited extremely long tracks of ssDNA in presence of replication stress, which were abrogated upon deletion of Exo1 [33] again consistent with our model.…”
Section: Low Dose Ddki Causes Aberrant Mitotic Structuressupporting
confidence: 85%
“…DDK is therefore required for the initiation of replicationcheckpoint activation, and we also show for the recovery of stalled forks. An active replicationcheckpoint would then attenuate nucleolytic activity at stalled forks to prevent excessive degradation of DNA by described mechanisms [41,[47][48][49]. Budding yeast cells lacking the checkpoint kinase Rad53, which inhibits DDK, exhibited extremely long tracks of ssDNA in presence of replication stress, which were abrogated upon deletion of Exo1 [33] again consistent with our model.…”
Section: Low Dose Ddki Causes Aberrant Mitotic Structuressupporting
confidence: 85%
“…hEXO1 is expressed at low levels in human nonproliferating tissues (23)(24)(25)(26), and the endogenous protein is barely detectable in total crude extracts from cell lines because of its low abundance and limited affinity to the available Abs (23). However, hEXO1 can be recovered and analyzed by Western blot analysis after immunoprecipitation.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in both human cells and budding yeast have indicated that phosphorylation of Exo1 negatively regulates its activity. Exo1 phosphorylation appears to be regulated by the Mec1/ATR pathways in budding yeast and human cells (11,30). Extrapolating to fission yeast, it is plausible that eliminating Rad3 enhances Exo1 activity and thereby allows Exo1 to substitute for Ctp1.…”
Section: Discussionmentioning
confidence: 99%